RESELIENSI MAHASISWA DALAM MENGHADAPI PEMBELAJARAN ONLINE DIMASA PANDEMI COVID-19 - Muchamad Suradji; Rizka Ananda Puspita Sari (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2022)
The Covid-19 pandemic has an impact on students studying from home online (online) during the quarantine period, which can reduce student motivation because learning satisfaction is disrupted. Psychological problems also arise, so that psychological resilience is needed to face unpleasant situations and the ability to adapt, namely academic resilience to be a factor in online learning satisfaction for students during the Covid-19 pandemic. Resilience is a personal quality that allows individuals to rise up when faced with adversity. This study uses a qualitative method with a phenomenological strategy which aims to describe the resilience of students in dealing with the COVID-19 pandemic at the Islamic University of Darul Ulum Lamongan. The average picture of the resilience of Darul Ulum Lamongan Islamic University students is in the medium category, meaning that students are still nervous in dealing with problems during the learning process from home, students are still not able to properly analyze the problem. Students have a desire to optimize their abilities in order to get maximum results.